Análise da bioética na Coréia - Yu, Kun Young (2010)
The present research aims at analyzing the Korean bioethics through the analysis of the historical, social, cultural and philosophical elements of the country to understand how such elements influenced in the constitution of bioethics in that country. The work is started through the study of scandal perpetrated by the major scientist of the country in the area, Professor Hwang Woo Suk, and by analyzing the social and political impact of such event we learnt about the values that guided the local bioethics, which are pragmatism and its strong social appeal. We will see how this science was skillfully handled for propagandistic purposes by the local government, upon attribution of a patriotic character to its development and the complicity with which an entire nation embraced this "national project" under which they placed expectations much beyond the medical benefits initially targeted. In the analysis of the factors that participated in the formation of this unique bioethics, we will analyze the association of the bioethical researches to the economic plans of the government, the influence of the several social and philosophical elements such as cultural hedonism, the local culture of pragmatic and empiric nature, the Silhak, the economic influence of the research for the community capitalism practiced in the country, and the patriotic appeal attributed thereto by the historical factors and principles such as Social Darwinism. The analysis of the aforementioned elements helps us to understand how a country so advanced in the researches on the biotechnology area, has a bioethics that is so weak in ethical content, that in last analysis it was responsible for the outbreak of the fraud in the stem cells cloning research